Determining if onsite water reuse systems make sense for your project - Hamilton, Jacob (Kansas State University, 2023)
Water is one of the most important natural resources to sustaining life on this planet. Fresh water quality and supplies are in decline throughout the world due to overuse, aging infrastructure, rapidly expanding communities, and changing climate and weather patterns. Recently several communities in the United States have been left without access to fresh potable water for extended periods of time due to these issues. To protect our water systems and make them more resilient, the adoption of onsite water reuse systems is becoming more prevalent. This report looks at the current state of water supplies and policy that dictate how we interact with the water cycle in the built environment. Several municipalities already require or incentivize the installation of onsite water reuse systems for new construction. It is a growing trend throughout the world, which plumbing designers and building owners will need to adapt to. This report discusses several concepts that will help with the design, installation, maintenance, and operation of these systems. The report also explores the relatively new concept of Net Zero Water; which both public and private organizations, such as the Living Building Challenge, have created framework for. An engineer working on these types of projects must know how to design for onsite water reuse systems. The design, calculations, components, and applications of several onsite water reuse systems are presented in this report.
Keywords: Onsite water reuse systems